2021
DOI: 10.3390/antiox10020153
|View full text |Cite
|
Sign up to set email alerts
|

How N-Acetylcysteine Supplementation Affects Redox Regulation, Especially at Mitohormesis and Sarcohormesis Level: Current Perspective

Abstract: Exercise frequently alters the metabolic processes of oxidative metabolism in athletes, including exposure to extreme reactive oxygen species impairing exercise performance. Therefore, both researchers and athletes have been consistently investigating the possible strategies to improve metabolic adaptations to exercise-induced oxidative stress. N-acetylcysteine (NAC) has been applied as a therapeutic agent in treating many diseases in humans due to its precursory role in the production of hepatic glutathione, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 118 publications
(288 reference statements)
0
16
0
Order By: Relevance
“…Previous research in men has reported an increase in total glutathione after intravenous NAC supplementation (Medved et al 2003 ) or that it remains stable after oral supplementation (Matuszczak et al 2005 ), and this may be due to equivalent changes in the reduced to oxidised glutathione ratio (Ferreira et al 2011 ; Matuszczak et al 2005 ). Our finding of a reduction in total glutathione during exercise may represent sex differences during exercise or a translation of NAC into specific pro-oxidants that were quenched by glutathione (Devrim-Lanpir et al 2021 ; Karimi et al 2016 ). For example, thiols were elevated in the plasma from acute NAC ingestion, which may have resulted in mixed disulphide formation.…”
Section: Nac and Exercise Physiologymentioning
confidence: 87%
“…Previous research in men has reported an increase in total glutathione after intravenous NAC supplementation (Medved et al 2003 ) or that it remains stable after oral supplementation (Matuszczak et al 2005 ), and this may be due to equivalent changes in the reduced to oxidised glutathione ratio (Ferreira et al 2011 ; Matuszczak et al 2005 ). Our finding of a reduction in total glutathione during exercise may represent sex differences during exercise or a translation of NAC into specific pro-oxidants that were quenched by glutathione (Devrim-Lanpir et al 2021 ; Karimi et al 2016 ). For example, thiols were elevated in the plasma from acute NAC ingestion, which may have resulted in mixed disulphide formation.…”
Section: Nac and Exercise Physiologymentioning
confidence: 87%
“…NAC has been considered a powerful antioxidant and glutathione precursor playing a crucial role in a variety of fields including athletic performance, respiratory complications, poisonings, infections, and cardiovascular diseases (Devrim‐Lanpir et al, 2021; Zarei et al, 2020). According to the available literature, there are some doubts about NAC side effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, other performance parameters such as lactate, pH, VO 2 , CK-MB, and CK were not assessed by the authors (Rhodes & Braakhuis, 2017). Also, a more recent narrative review presented the NAC effects on exercise-induced oxidative stress (EIOS) and athletes' adaptive responses (Devrim-Lanpir et al, 2021). To our knowledge, no study has attempted to run a systematic review and meta-analysis on NAC and recovery parameters (lactate, pH, VO 2 , CK, and CPK).…”
Section: Mahmoud Et Al Indicated That Acute Nac Administration In Pat...mentioning
confidence: 99%
See 1 more Smart Citation
“…The review by Devrim-Lanpir et al [ 2 ] focuses on the induced effects of using N-acetylcysteine (NAC) due to its precursor role in the production of hepatic glutathione, a natural antioxidant that can significantly modulate exercise-induced oxidative stress. In the various studies considered by the authors, a possible therapeutic role for NAC in oxidative metabolism and the adaptive response to exercise is not always clear-cut.…”
mentioning
confidence: 99%